Analysis of the Effect of Service Quality on Loyalty in Banking Customers - Cuandra, Fendy; Wijaya, Calvin; Candy, Candy (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This research aims to understand the impact of service quality, trust, brand image, brand awareness, and CSR (Corporate Social Responsibility) on customer loyalty, with customer satisfaction as an intervening variable in conventional banks. This research is grouped as causal-comparative research. This study targets Batam conventional banks as the subject. Purposive sampling is used to select samples, and the selected samples must meet certain requirements. Bank Rakyat Indonesia, Bank Central Asia, and Bank Negara Indonesia were chosen as samples because they were recipients of the title "The Most Reliable Bank" at the 2022 Indonesian Banking event. The research sample consisted of 342 respondents who were customers of Batam conventional banks. Collecting data information through distributing questionnaires was carried out using digital media such as Google Forms. The data analysis method used is partial least squares analysis using the SmartPLS version 3.0 tool. The research results show that brand image, service quality, and brand awareness can significantly influence customer loyalty. However, corporate social responsibility is not able to provide a significant influence on customer loyalty. Apart from that, rust is not able to have a significant impact on customer loyalty, which is moderated by customer satisfaction.